Studi Deskriptif Tingkat Toleransi Beragama dan Kematangan Beragama di Kota Tangerang - Roebianto, Adiyo; Hikmah, Wenny; Putri, Iga Nadilah (TAZKIYA Journal of Psychology, 2021)
Tangerang is a city whose people consist of various ethnicities or religions, such as Muslims, Christians, Catholics, and Buddhists. Even in Tangerang, there are quite a lot of temples / temples. In the last 20 years, the people of Tangerang City have never faced horizontal conflicts between religious believers. But interestingly, based on the results of the Setara Institute study in 2018, Tangerang as a city has a tolerance index of 4.58 from a range of scores of 1-7. This figure puts Tangerang in the 61st position of the 94 cities surveyed. These results can be said to be low. Of course, this is somewhat different from the phenomenon which recorded the absence of horizontal conflicts in Tangerang City. The purpose of this research is to see a picture of religious maturity and religious tolerance in the people of Tangerang city. This study used a quantitative approach, target participants in this study were 150 (n = 150) participants. The research instrument was a questionnaire containing statements / items related to religious tolerance. Data was collected by means of online administration because this study was conducted during the Covid-19 pandemic. The results of the mean difference test show that there is no significant difference, both in terms of religious tolerance and religious maturity based on the demographic group of age, gender, and education. But in terms of histogram distribution, it shows the outlier score on the variable of religious maturity. Therefore, in general, demographic factors do not affect the variation of religious tolerance and religious maturity. However, the religious maturity score of the people of Tangerang City is relatively low.